Evolution of antibiotic prescription in Primary Health Care according to the indicators of the Spanish Action Plan on Antibiotic Resistance (PRAN) - Carlos Marcilla Vázquez; Juan Ríos Laorden; Ángeles Lloret Callejo; Francisco Tejada Cifuentes; María José Tirado Peláez; Ignacio Párraga-Martínez (Anales de Pediatría (English Edition))
Introduction: Spain is the fourth European country with the highest antibiotic consumption at the community level, being children aged 0-4 years one of the age groups with the highest amount of consumption. The aim of this study was to analyze the evolution of antibiotic prescription of the pediatric population in a Primary Health Care area according to the indicators of the Spanish Action Plan on Antibiotic Resistance (PRAN) in a period of ten years (2014-2023), as well as to evaluate the impact of the COVID-19 pandemic by the comparison between 2020-2021 years and a previous (2014-2019) and a later periods of time (2022-2023). Material and methods: Retrospective observational study of the prescription of antibiotics for systemic use (J01 group of the Anatomical Therapeutic Chemical Classification) in pediatric patients (0-14 years) belonging to the Primary Health Care area of the Gerencia de Atención Integrada (GAI) de Albacete between 2014 and 2023. Results: Mean antibiotic prescription was 16.90 defined daily doses per 1000 inhabitants per day (DID) and 12.10 DOT (days of therapy). Pre-pandemic data (2014-2019) was 19.32 DID and 13.92 DOT, being reduced during the two years of the pandemic (2020-2021) to 8.30 DID and 6.05 DOT and subsequently increased to 18.05 DID and 12.40 DOT in post-pandemic years (2022-2023). An improvement in the adequacy of antibiotic prescription was observed after the COVID-19 pandemic, with a reduction of the consumption of amoxicillin-clavulanate and a greater consumption of penicillin and amoxicillin during pre-pandemic and pandemic years (p < 0.05). Conclusions: Thoughout the period of years analysed, an improvement in the consumption indicators proposed by the PRAN, with a higher use of beta-lactamase sensitive penicillins and amoxicillin and a reduced consumption of amoxicillin-clavulanate. Resumen: Introducción: España es el cuarto país europeo con mayor consumo de antibióticos a nivel comunitario, siendo los niños de 0-4 años uno de los rangos de edad de mayor consumo. El objetivo de este estudio fue analizar la evolución de la prescripción de antibióticos en la población pediátrica de Atención Primaria de un área Sanitaria en función de los indicadores del PRAN durante diez años (2014-2023), así como, evaluar el impacto de la pandemia de COVID-19 comparando el periodo 2020-2021 respecto al previo (2014-2019) y posterior (2022-2023). Material y métodos: Estudio observacional retrospectivo de prescripción de antibióticos sistémicos (grupo J01, clasificación Anatomical Therapeutic Chemical Classification) en población pediátrica (0-14 años) en el ámbito de Atención Primaria de la Gerencia de Atención Integrada (GAI) de Albacete entre 2014 y 2023. Resultados: La prescripción media de antibacterianos fue de 16,90 dosis diaria definida por 1000 habitantes/día (DHD) y 12,10 DOT (days of therapy). Los datos prepandemia (2014-2019) fueron de 19,32 DHD y 13,92 DOT, reduciéndose durante la pandemia (2020-2021) hasta 8,30 DHD y 6,05 DOT y aumentando, posteriormente (2022-2023), hasta 18,05 DHD y 12,40 DOT. Se observó una mejora en la adecuación de la prescripción tras la pandemia, con menor utilización de amoxicilina/clavulánico y mayor de penicilina y amoxicilina que antes y durante pandemia (p < 0,05). Conclusiones: A lo largo del periodo estudiado se observó una mejoría de los indicadores de consumo propuestos por el PRAN, mostrando mayor uso de penicilinas sensibles a betalactamasas y de amoxicilina, y menor consumo de amoxicilina/clavulánico.